Darkening of the Svalbard Fjords Waters Observed With Satellite Ocean Color Imagery in 1997–2019 - Konik, Marta; Darecki, Mirosław; Pavlov, Alexey K.; Sagan, Sławomir; Kowalczuk, Piotr (Frontiers in Marine Science, 2021)
Global warming is not often discussed in the context of light availability within the water column. However, the light regimes in the Arctic Ocean are controlled by three factors that are influenced by climate changes which are the sea ice albedo feedback, glacial meltwater runoff and marine primary production. Based on a satellite data series acquired during time period 1997 – 2019, we inspected long-term changes of the three commonly used optical characteristics Chla, atot(443), and Kd(490) within the Svalbard fjords and on the West Spitsbergen Shelf. We revealed evident positive trends in summer (July – September) in the Isfjorden, the Kongsfjorden, the Hornsund fjord, and the Bellsund. Moreover, between 1997 and 2019 at the majority of locations we observed a regime shift toward darker waters. We showed that light availability has changed in the Svalbard fjords since 1997, which may be a symptom of transformations in the environment that should be further investigated and monitored.